The perceptions of stakeholders of the implementation of a state funding model in South African public schools. Issue 2 (2nd April 2016) - Mestry, Raj; Berry, Brian
ABSTRACT: The government has made great strides in redressing past imbalances in education through the National Norms and Standards for School Funding (NNSSF) policy that focuses on equity in school funding. This NNSSF model compels the state to fund public schools according to a poverty quintile system, where poor schools are allocated much more funding for resources than affluent schools. Using qualitative research, school management teams, school governing bodies and principals of six public schools located within the Gauteng West District were interviewed to determine their views of how the NNSSF policy had been implemented. One of the findings revealed that equity in public schools has not been fully achieved since funding provided by the state is insufficient to address the backlog in educational resources. It is recommended that the state abandons the policy of funding schools according to quintile rankings but instead, fund schools based on resource needs.